UNIVERSITY SUMMER SCHOOL: THE TECHNOLOGY OF ORGANIZATION AND LEARNING - I. B. Nazarova (Высшее образование в России)
The article highlights the role ofsummer schools at universities. Methods and empirical base: content analysis of the summer school's resources. The materials of 128 summer schools in Russian and foreign universities (2013-2015) were analyzed. 26 interviews of the schools' organizers were collected and analyzed. University Summer School is the form of life learning, career and recreation. It helps in getting new knowledge, skills, competencies on major and other branches of studies, in developing interdisciplinary fields, and lets students be involved in research and practical activity. Summer school activities positively influence on corporate culture, provide the special atmosphere of interaction between academic staff and students. The activities encourage the formation of regional and international professional network by interest. Personal contacts make special academic environment. Summer schools create a positive university image and become a kind of university business card, a university brand. They can promote the implementation of the university's social mission, strengthen public relations.